Heaven as the Outermost Periphery of the Earth in Archaic Ionian Cosmologies - Kočandrle, Radim (Hyperboreus, 2022)
The conception of heaven in archaic Ionian cosmologies, which belong to the earliest Presocratic conceptions of the world, is due to meagre textual evidence hard to reconstruct. Current scholars, meanwhile, tend to agree that in the previous epic tradition, heaven was believed to form a firm hemisphere located above a flat earth. Although such interpretations are based on indirect evidence, one can suppose that during the Archaic Era, heaven was considered to be a concrete constituent of the universe with a particular composition. In the case of archaic Ionian cosmologies, one can assume – based on their meteorological nature and the assumption of movement of heavenly bodies only above the earth – that the space of the universe stretched only between a flat earth and the heaven. The entire universe was thus viewed as closed, with the heaven forming its upper limit. Still, the heaven need not have been imagined as hemispherical: it could have been thought flat or merely curved. To wit, one can argue that the hemispherical shape of heaven, which often features in current interpretations, anachronistically draws on later conceptions belonging to the Italian school of philosophy, where the universe and therefore also the heaven was believed to form a sphere.